Category of equivalence in G. Turi’s concept - Нуреловa, A. М. (Journal of Oriental Studies, 2018)
In this article the category of equivalence in the descriptive concept of G. Turi is considered. And also his researches in this area and what part is assigned by G. Turi to category of equivalence in theory of translation